Peran Aktor dalam Pengelolaan Objek Wisata Panorama Tabek Patah di Kabupaten Tanah Datar - Hardianti, Siti; Jumiati, Jumiati (Policy, Law and Political Research Center, 2023)
This study aims to analyze and determine the role of actors in the management of the Tabek Patah Panorama tourist attraction, Tanah Datar Regency. This research is processed by technical analysis qualitatively with descriptive methods, data collection techniques are carried out through interviews, observation and documentation. While the analysis technique is through the MDAP technique (Manual Data Analysis Procedure).The results show that the management of the Tabek Patah Panorama Tourism Object involves the roles of the three actors, namely the government, the community and the private sector. The local government through the Tanah Datar Tourism Office and the Tabek Wali Nagari Wali has tried to carry out its role as Motivator, Facilitator, although there are still obstacles in the implementation of this role. The community as one of the actors who are targeted in the development of Tabek Patah Panorama Tourism Object provides a participation role in the management of Tabek Patah Panorama as in the role of ideas in the form of facilities and input, the role of Energy, the role of Assets / Objects, the role of skills / abilities and social roles. And the private sector as one of the actors who play a role in supporting the management of the Panorama Tabek Patah tourist attraction provides its role in the form of providing accommodation facilities, transportation, entertainment facilities, shopping shop facilities and providing support for tourist attractions. The three actors in carrying out their roles are also influenced by several supporting and inhibiting factors.